The role and significance of honorifics with special reference to Xitsonga discource - Makhubela, Anania Hazel (2004, 2004)
Refer to the document
Thesis (M. A. (African Languages)) -- University of Limpopo, 2004
Keywords: Honorifics; Xitsonga language; Discourse analysis; Grammar, Comparative and general -- Honorific; Tsonga language -- Honorific; Tsonga language -- Discourse analysis